Compact Modified Swastika Shape Patch Antenna for WLAN/WiMAX Applications. (27th April 2014) - Samsuzzaman, M.; Islam, T.; Abd Rahman, N. H.; Faruque, M. R. I.; Mandeep, J. S.
Abstract : A compact simple structure modified Swastika shape multiband patch antenna is designed and investigated. The antenna, which occupies an overall dimension of 0.305 λ × 0.305 λ × 0.012 λ at lower frequency, has a simple structure which comprises of a planar wide square slot in the ground with four slits and Swastika shape radiation patch with a rectangular slot. The proposed Swastika shape antenna was designed and analyzed by using a finite element method based high frequency structural simulator HFSS. The experimental and numerical results exhibit that the antenna operates over the frequency ranges 950 MHz (2.28–3.23 GHz), 660 MHz (3.28–3.94 GHz), and 1120 MHz (5.05–6.17 GHz) suitable for WLAN (2.4/5.2/5.8 GHz) and WiMAX 2.5/3.5/5.5 GHz applications. It has a good omnidirectional radiation pattern and reaches 3.97 dBi at 2.44 GHz, 4.04 dBi at 3.5 GHz, and 3.25 dBi at the band of 5.98 GHz. A prototype is fabricated and then measured. The experimental and simulation results show good impedance bandwidth, radiation pattern, and stable gain across the operating bands.